SISTEM PENDUKUNG KEPUTUSAN PENETAPAN TUNJANGAN PRESTASI DENGAN MENGGUNAKAN METODE FUZZY-TSUKAMOTO - Yusron Rijal; Yus Amalia (Jurnal Matematika MANTIK, 2016)
The high quality of human resourches according the expertise and competence is needed for increasing factory productivity. According the employee’s expertise and competence, it’s required for giving appreciation for the working achievement for motivated to increase the working achievement. In awarding the decision of giving appreciation, in this case feat allowance required for the performance appraisal is expected to assist in delivering the right decisions and avoid subjectivity. Employees deserve appreciation if the result of the performance evaluation meets the criteria specified by the company, the job performance, work quality, dicipline, responsibilities, absenteeism and konduite. Decision support systems is apt to be applied in the decision giving appreciation. The decision support system performance allowance is using fuzzy Tsukamoto. The result showed that the reasoning in the process of data input and output can analyze whether or not the provision of benefits achievement, this system can help accurately make decisions feasibility of providing allowances achievement with the accuracy of 100% and the amount of allowances achievement of 94.71% using the method of system testing the Black Box Testing